FoMO (Fear of Missing Out) Tendency in Millennials - Maysitoh Maysitoh; Ifdil Ifdil; Zadrian Ardi (Indonesian Institute for Counseling, Education and Theraphy, 2020)
As a generation that grows in the era of internet and digital advancement, millennial generation is the generation that is always connected to each other (always connected generation). The high level of use of social media in this generation has raised concerns about the consequences of problems related to the use of social media in this group. One of them they try and have a desire to continue to connect with what is being done by others through cyberspace so as to cause anxiety in themselves and lead to a fear, which is the fear of being left behind. This phenomenon is called FoMO (Fear of Missing Out). This study describes the level of FoMO inclination in Padang State University students. The sample used was 416 respondents spread throughout the faculties and the sampling was done using propotional random sampling technique. The instrument used was a closed questionnaire using a Likert scale model. The data obtained were analyzed using percentage techniques. The results of the study in general showed that the tendency of FoMO in students was in the low category at 47.59%.